The Impact Of Workload, Job Satisfaction And Job Burnout On Turnover Intention Nurses In The Public Hospital - Lestari, Fuza; Amalia, Fina; Sunimah (PT FORMOSA CENDEKIA GLOBAL, 2024)
This research aims to determine the influence of workload, job satisfaction, and work fatigue on nurse turnover intention. This research used quantitative methods with a population of nurses at regional general hospitals using a non-probability purposive sampling technique involving 150 respondents out of a total of 288 nurses. The analysis technique was carried out using multiple regression analysis with SPSS 26. Data was collected through a questionnaire using a Likert scale measurement instrument. The results of this study indicate that workload has an insignificant effect on the intention to change jobs. Meanwhile, job satisfaction has a negative and significant influence on turnover intention. Apart from that, job fatigue has also been proven to have a negative and significant influence on the intention to change jobs. Furthermore, there is a simultaneous influence of the variables workload, job satisfaction, and job fatigue on the intention to change jobs.